Sensory Pollution from Treated Wood Panels on Perceived Air Quality and Human Comfort - El Danaf, Taher Salah (2013)
The aim of the present study is to examine the effects of sensory pollution from treated wood panels, commonly used in the United Arab Emirates (UAE), on perceived air quality (PAQ) and human comfort. Human subjects between 20 and 30 years of age, recruited from the university community evaluated the air upstream of four different wood panels placed in a ‘small’ chamber of 0.216m3. The evaluated wood panels included: ‘wood panel with water-based paint’, ‘wood panel with oil-based paint’, ‘wood panel with melamine urea formaldehyde’ (MUF), ‘normal MDF sample’ (Medium Density Fiberboard) without any additives’. Additionally, assessment was done when the chamber was ‘empty’. These conditions were assessed in random order. Furthermore, each of the conditions was assessed when a fan, placed in the chamber below the samples, was turned ‘on’ or ‘off’. Hence, a total of 10 conditions were evaluated. Assessments were done by 20 subjects. The subjects, blinded to the 10 conditions, evaluated their level of air acceptability and freshness of air coming out of the chamber. Odour intensity and noise irritation arising from assessed air were also evaluated. Air acceptability values were used to calculate percentage of subjects’ dissatisfactions for each condition. The air upstream of ‘wood panel painted with oil based paint’ was judged to significantly deteriorate PAQ and caused most discomfort to the subjects. Unpredictably, the UF sample assessment was equal to water based-paint sample in both chamber conditions, this indicated that subjects are accustomed to this odour in their lifestyle and experience expectations. Female results in gender comparison showed higher levels of sensory pollution to all samples. Use of fan generally improved PAQ. Understanding from this study is relevant to creating healthy indoor environment for building occupants.